Analisis Ijab Qabul dalam Pernikahan Islam Melalui Pendekatan Hermeneutik - Dinata, Rangga Iskandar; Muqowwim (TERAJU: Jurnal Syariah dan Hukum, 2023)
This research aims to discuss ijab qabul in Islamic marriage which will be analyzed through a hermeneutic approach. Basically, the use of ijab qabul is the sentence nikah or tazwij. This research is a literature research using an analytical descriptive hermeneutic approach. The objectives of this study are 1) to analyze hermeneutics in Islamic studies, 2) to analyze ijab qabul using a hermeneutic approach. The results of the study explain that the Hanafi and Maliki madhhabs argue that it is permissible to use sentences other than nikah and tazwij as ijab qabul provided that they must have the same meaning and in accordance with Islamic demands. So that the marriage is still considered valid. Meanwhile, the Shafi'i and Hanbali schools argue the opposite, that the consent of marriage must use the phrase nikah or tazwij.